Indonesia Hospital Cost Analysis: a Micro-Costing Approach (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
Efforts to develop the financing methods is needed to strengthen the Indonesia’s recently implemented universal health coverage system. Hospital cost data is urgently needed to calculate the unit cost of medical services that is important to evaluate the reimbursement rate setting. The most recent approach to calculate unit cost of medical services in hospital is micro-costing approach. This study aimed to perform a unit cost calculation using micro-costing approach in Indonesia’s district hospital in June-Dec 2016 from the provider perspective. The costing study followed the standard costing method and financial data were obtained through the hospital financial reports. Some financial data were directly measured since this study used bottom-up approach. This study showed that the unit cost was not relevant with the reference price set up by the government. It could be caused by different cost items and cost objects that had been employed in the study since the government tariff’s did not have clear and detailed information about the source of cost calculation. Micro-costing approach was useful as a precise method to calculate unit cost, even though rigorous efforts were needed to complete the data.